Public redistribution and voter demand: The middle class as a modern Robin Hood? - Ursula Dallinger (Luxembourg Income Study (LIS), 2015)
Over the last few decades government income redistribution cushioned the growing disparity in the distribution of market incomes in many highly industrialized countries. There is a controversy in comparative political economy on what determines the varying scope of redistribution. The paper addresses, whether redistribution reacts to growing inequality and to demands by middle class voters harmed by economic change, or whether it is determined by political parties and institutions. It focuses on the hypothesis of distributional coalitions constituted from lower and middle classes and facilitated by 'affinity' due to changing income structures. The analysis used micro-data from the Luxembourg Income Study which were supplemented with other variables to yield a 'pooled cross-sectional time series' of 81 observations in 19 countries for the period 1980 to 2005. The results do not support a similarity of income positions of middle and lower income classes as basis for cross class coalitions, but underscore growing distances because of losses of income position of the poorest. Hence, political factors must be decisive. Power re-sources of left parties and their shift to the middle of the left-right-axis and welfare state institu-tions had just a small impact. Voter-turnout and electoral institutions were more influential for redistribution.
Keywords: 330